Foreign aid and soft power diplomacy: Azerbaijan’s response to global development crisis in Africa - Huseynova, Fatima; Pashayeva, Fatima; Kerimli, Nushaba (ADA University, 2024)
In contemporary world politics concept of soft power occupies an important place. States prefer to shape the policy preferences of other countries non-coercively through cultural, diplomatic, and political means rather than coercion. Azerbaijan has huge potential for soft power and can project it to many regions by, for example, providing aid. Azerbaijan regularly provides aid to African countries through Azerbaijan International Development Agency (AIDA). The question this paper attempts to answer is how to transform the aid provided by Azerbaijan to African nations into a soft power. This capstone project highlights the problems that hinder the effectiveness of such transformation such as the focus on short-term humanitarian rather than long-term development aid, insufficient usage of Public Relations tools, and lack of sustained contact with African graduates of the higher education institutions of Azerbaijan. Policy solutions for each of these problems are proposed – advancing initiatives for long-term solutions for visual impairments and preventive healthcare in the African region, expanding AIDA’s engagement with effective Public Relations tools, and establishing associations of African alumni of Azerbaijani universities. These solutions were evaluated using five key criteria – effectiveness, efficiency, equity, feasibility, and flexibility. This paper relied heavily on primary data obtained from the interviews and secondary data extracted from journal articles, books, and official websites of such agencies and state institutions as MFA, AIDA, OECD, UNHCR, and others. This project concludes that AIDA, higher education institutions, and Azerbaijani diplomatic missions abroad should all work in tandem and do their part to further Azerbaijan’s soft power in Africa.
Keywords: Azerbaijan -- Foreign relations -- Africa; Azerbaijan -- Foreign aid; Public relations -- Azerbaijan; Diplomatic relations -- Azerbaijan; Public and International Affairs